Evaluations of morpho-physiological variances in soybean varieties under low water conditions - Mangena, Phetole; Mabulwana, Paseka Tritieth (Journal of Experimental Biology and Agricultural Sciences, 2022)
This study used pot experiments with a completely randomized design (CRD) in triplicates to evaluate physiological and morphological attributes used for the characterization of drought stress tolerance in six soybean varieties (Knap, Mopani, LS677, LS678, Pan1564, and Sonop). Growth and physiological parameters analyzed in this study, included plant height, number of flowers, number of pods, seed number per pod, leaf surface area (LSA), grain yield, and total phenolics, flavonoids, ureides as well as antioxidant activity. Low water conditions caused varied negative effects depending on the level of stress on both morphological and physiological responses of the plants. Enhanced secondary products (ureides, total phenolic, and flavonoid content) were observed in plants subjected to severe water stress, in addition to reduced photosynthetic components and percentage grain yields. However, soybean variety Sonop, LS677, and LS678 consecutively, induced high secondary metabolite accumulations and antioxidant activity possibly preventing the occurrence of excessive oxidative stress damage caused by water shortage. The performance of LS varieties, Knap and Sonop were more prominent than Mopani and Pan1564. Results showed potential tolerance to stress in Sonop, LS678 and LS677, attributed to the strong free radical scavenging activity and maintenance of photosynthetic pigments used to achieve sufficient growth balance in plants.
Journal article published in Journal of Experimental Biology and Agricultural Sciences, February - 2022; Volume – 10(1) page 12 – 20
Keywords: Antioxidant activity; Chlorophyll; Flavonoid content Phenolics; Soybean; Water-deficit stress; Strains and stresses; Biodivesity; Chlorophyll; Soybean